2012
DOI: 10.4103/0970-0358.96593
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical basis of dimple creation - A new technique: Our experience of 100 cases

Abstract: Background:Cheek dimples are usually considered as an attractive feature of facial beauty. Unfortunately, not all beautiful girls have dimples. Literature on dimple creation surgery is sparse.Aims:We used a new and simple technique for dimple creation, passing a transcutaneous bolster stitch after scraping off the dermis of all mucomuscular attachments. Our aim was to analyse the positive and negative findings of this technique.Materials and Methods:We used this procedure in creation of 100 dimples under local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Lari described a similar procedure in which bolsters were placed on the skin and intraorally and left for 7 days. 5 Over time, the suture fixation may fail; however, the procedure can be repeated.…”
Section: Disscusionmentioning
confidence: 99%
“…Lari described a similar procedure in which bolsters were placed on the skin and intraorally and left for 7 days. 5 Over time, the suture fixation may fail; however, the procedure can be repeated.…”
Section: Disscusionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Excessive scarring secondary to foreign body reaction or infection with abscess formation is also uncommon but can result in disfigurement. [1][2][3] In general, open techniques have more risk of complications because more tissue is resected, in contrast to closed techniques with little tissue defect. [1][2][3][4][5][6] Nonabsorbable sutures that are kept for a long time tend to have an increased potential risk of complications than that of absorbable sutures because they increase the risk of foreign body reaction and provide an access point for food debris, dental plaques, and oral actinomyces.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other techniques-particularly, open technique-no tissue is resected, and no suture (whether permanent or absorbable) is left behind, thus minimizing risk of hematoma and infection. 3 Poor condition of the oral and dental tissue increases the risk of infection as well. Actinomyces are gram-positive filamentous bacteria that are commensals in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…With refinement in surgical technique, there is an increasing demand for dimple creation surgery. In one center in Maharashtra (India), authors have reported creation of 100 dimples in the period 2006–2010 …”
Section: Dimple Surgerymentioning
confidence: 99%
“…In one center in Maharashtra (India), authors have reported creation of 100 dimples in the period 2006-2010. 42…”
Section: Dimple Surgerymentioning
confidence: 99%